Pronunciation Assessment: Traditional vs Modern Modes - Ali Babaeian (Journal of Studies in Education, 2024)
Pronunciation assessment is a crucial component of language teaching and learning. Nonetheless, there seems to be a lack of consensus on the best methods and criteria for evaluating learners’ pronunciation. This review provides an overview of the traditional and modern modes of pronunciation assessment, highlighting their strengths and limitations and their approaches to assessing pronunciation. Traditional modes solely rely on human raters’ judgments and linguistic knowledge and may be encroached upon on various grounds. Modern modes often use artificial intelligence, automatic speech recognition, and complicated programs to measure and score pronunciation features. The review concludes with some implications and future directions for modern modes of pronunciation assessment.